2013
DOI: 10.1007/s12298-013-0195-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and differential expression studies of an oxidosqualene cyclase (OSC) gene of Brahmi (Bacopa monniera)

Abstract: Triterpenoid saponins are the class of secondary metabolites, synthesized via isoprenoid pathway. Oxidosqualene cyclases (OSCs) catalyzes the cyclization of 2, 3-oxidosqualene to various triterpene skeletons, the first committed step in triterpenoid biosynthesis. A full-length oxidosqualene cyclase cDNA from Bacopa monniera (BmOSC) was isolated and characterized. The open reading frame (ORF) of BmOSC consists of 2,292 bp, encoding 764 amino acid residues with an apparent molecular mass of 87.62 kDa and theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…We chose BmOSC (Accession number. HM769762.1) as a control, which did not meet any of our screening criteria but was annotated as “putative β-AS” in a previous study …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose BmOSC (Accession number. HM769762.1) as a control, which did not meet any of our screening criteria but was annotated as “putative β-AS” in a previous study …”
Section: Results and Discussionmentioning
confidence: 99%
“…Lots of triterpenoids, especially ursolic acid and oleanolic acid were main components of apple peels, which were catalyzed by CYP450 enzyme with α-amyrin and β-amyrin as precursors, respectively , Phylogenetic analysis revealed that BmOSC is closely related with other plant OSCs, especially mixed α-AS, suggesting that BmOSC may be involved in formation of pentacyclic triterpenoids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the DCTAE motif might be crucial for the interaction between the protein and its substrate [ 38 ]. The QW repeat is a negatively charged aromatic region that equalizes carbocation in the cyclization reaction, which may play a role in the structural stabilization of proteins [ 39 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…A fulllength oxidosqualenecyclasec DNA from Bacopa monnieri oxidosqualenecyclases (BmOSC) has been isolated and characterized. Quantitative realtime PCR (qRT-PCR) data showed that BmOSC is expressed in all tissues examined with higher expression in stem and leaves as compared to roots and floral parts 96 . A full-length SQS gene has also been isolated from B. monnieri and characterized as B. monnieri squalene synthase (BmSQS) (1242 bp) encoding 414 amino acids.…”
Section: Analysis Of Metabolic Pathway Gene Expressionmentioning
confidence: 99%